Acquisition of antimicrobial-resistant bacteria in the absence of antimicrobial exposure: A systematic review and meta-analysis. (29th July 2019) - D'Agata, Erika M. C.; Geffert, Sara F.; McTavish, Rebecca; Wilson, Florence; Cameron, Chris
Abstract: Objective: The main risk factor for acquisition of antimicrobial-resistant bacteria (ARB) is antimicrobial exposure, although acquisition can occur in their absence. The aim of this study was to quantify the proportion of patients who acquire ARB without antimicrobial exposure. Study design: We searched Medline, Embase, and the Cochrane library for publications between January 1, 2000, and July 24, 2017, to identify studies of ARB acquisition in endemic settings. Studies required collection of serial surveillance cultures with acquisition defined as a negative baseline culture and a subsequent positive culture for an ARB, including either multidrug-resistant gram-negative bacteria or antimicrobial-resistant enterococci. Intervention studies were excluded. For each study, the proportion of patients who acquired an ARB but were not exposed to antimicrobials during the study period was quantified. Results: A total of 4, 233 citations were identified; 147 underwent full-text review. Of these, 10 studies met inclusion criteria; 7 studies were considered to be at low risk of bias; and 6 studies were conducted in the intensive care unit (ICU) setting. The overall summary estimate for the proportion of patients who were not exposed to antimicrobials among those who acquired an ARB was 16.6% (95% CI, 7.8%–31.8%; P < .001), ranging from 0% to 57.1%. We observed no heterogeneity in the ICU studies but high heterogeneity among the non-ICU studies. Conclusion: In most included studies, a subset of patients acquired an ARB but were not exposed to antimicrobials. Future studies need to address transmission dynamics of ARB acquisition in the absence of antimicrobials.